Estrutura de governança no arranjo produtivo local do açaí no município de Igarapé-Miri - COELHO JUNIOR, Francisco de Paulo (Universidade Federal do Pará, 2019)
Endogenous development is an alternative capable of transforming productive units at the local level, in order to transform them substantially, to the point of resulting in significant economic and social advances. Initiatives in this way can establish forms of governance shaped by the creation of interaction bonds and cooperation mechanisms. Therefore, the purpose of this essay is to describe the structure that defines governance in the Local Productive Arrangement of açaí in the municipality of Igarapé-Miri, seeking to know how the relationship between agents can influence local development. For this, a bibliographical and field research was developed, whose qualitatively presented results are described in a way that clearly and objectively demonstrates the local reality. The data collected and analyzed reveal the path that Igarapé-Miri followed to constitute a Local Productive Arrangement and to become the "Acaí World Capital", besides demonstrating the existing governance structure around the açaí commercial activities at the municipal level, represented by the way of acting and by the relation existing between the main agents of the Arrangement.